The Emerging Roles of the Adaptive Immune Response in Acute Pancreatitis - Bojan Stojanovic; Ivan P. Jovanovic; Milica Dimitrijevic Stojanovic; Marina Jovanovic; Berislav Vekic; Bojan Milosevic; Aleksandar Cvetkovic; Marko Spasic; Bojana S. Stojanovic (Cells, 2023)
Acute pancreatitis (AP) is an abrupt, variable inflammatory condition of the pancreas, potentially escalating to severe systemic inflammation, rampant pancreatic necrosis, and multi-organ failure. Its complex pathogenesis involves an intricate immune response, with different T cell subsets (Th1, Th2, Th9, Th17, Th22, TFH, Treg, and CD8+ T cells) and B cells playing pivotal roles. Early T cell activation initiates the AP development, triggering cytokines associated with the Th1 response, which stimulate macrophages and neutrophils. Other T cell phenotypes contribute to AP’s pathogenesis, and the balance between pro-inflammatory and anti-inflammatory cytokines influences its progression. Regulatory T and B cells are crucial for moderating the inflammatory response and promoting immune tolerance. B cells further contribute through antibody production, antigen presentation, and cytokine secretion. Understanding these immune cells’ roles in AP could aid in developing new immunotherapies to enhance patient outcomes. However, further research is required to define these cells’ precise roles in AP and their potential as therapeutic targets.